(untitled) (Journal of Social Economics Research, 2026)
The transition from centrally planned economies toward market-oriented economies provides a unique context for fostering entrepreneurship. However, entrepreneurship is related to many social and economic issues, but its association with democracy lacks empirical validation and remains largely theoretical. This study explores the relationship between democracy and entrepreneurship in transitional economies. Comprehensive measures of ET and DCs are employed for empirical investigation, which are often overlooked in the context of transitional economies. The panel data of 15 transitional economies from 2014 to 2019 are analyzed. Panel data techniques such as Fixed Effects model with Driscoll-Karaay Standard Error (FE-DKSE), Feasible Generalized Least Squares (FGLS), and Panel-Corrected Standard Error (PCSE) methods are used for empirical analysis. The findings indicate that ET and DCs are associated in transitional economies. A positive and statistically significant relationship exists between ET and DC. DC boosts ET in these transitory nations. The inclusion of other covariates, such as financial development (FD), foreign direct investment (FDI), and technological innovations, does not affect the core findings. These covariates also have favorable effects on ET in these countries. The empirical results suggest that democracy in transitional economies, by ensuring accountability and reducing organizational uncertainty, creates an environment conducive to entrepreneurial activity.